2009
DOI: 10.1158/0008-5472.can-08-2354
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Phosphoproteomics Reveals a Cluster of Tyrosine Kinases That Mediates Src Invasive Activity in Advanced Colon Carcinoma Cells

Abstract: The nonreceptor tyrosine kinase Src is frequently overexpressed and/or activated in human colorectal carcinoma (CRC), and its increased activity has been associated with a poor clinical outcome. Src has been implicated in growth and invasion of these cancer cells by still not well-known mechanisms. Here, we addressed Src oncogenic signaling using quantitative phosphoproteomics. Src overexpression increased growth and invasiveness of metastatic SW620 CRC cells. Stable isotope labeling with amino acids in cell c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
127
3
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(145 citation statements)
references
References 42 publications
14
127
3
1
Order By: Relevance
“…This mechanism may particularly operate in advanced CRC cells, in which tumour cells harbour maximal Csk membrane delocalization together with a high SFK level. In this respect, a moderate expression of wild-type Src in advanced CRC SW620 cells is sufficient to increase oncogenic properties, in particular, the proinvasive activity (Leroy et al, 2009). This may explain why CRC cells can withstand high Csk levels, as observed in tumour biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism may particularly operate in advanced CRC cells, in which tumour cells harbour maximal Csk membrane delocalization together with a high SFK level. In this respect, a moderate expression of wild-type Src in advanced CRC SW620 cells is sufficient to increase oncogenic properties, in particular, the proinvasive activity (Leroy et al, 2009). This may explain why CRC cells can withstand high Csk levels, as observed in tumour biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…The identity of this protein was unravelled via a SILAC-based quantitative proteomic analysis, which allowed the identification of SLAP interactors in tumour cells including those phosphorylated on tyrosine residues. A prominent interactor isolated was EPHA2, which we recently described as an important SRC substrate for oncogenic signalling 11 . While SLAP was originally identified by its binding capacity to EPHA2, their interaction has never been addressed in vivo 21 .…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, upregulation of wild-type SRC in advanced tumour stages may be sufficient to induce oncogenic signalling. A previous phosphoproteomic analysis revealed that SRC phosphorylates a cluster of TK, including the receptors MET and EPHA2 that mediate CRC cell tumorigenicity and invasiveness 11 . How SRC elicits the activation of these RTK was previously unclear but the present study describes a mechanism that favors SRC-EPHA2 interaction through receptor stabilization following SLAP inactivation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations